Peran Literasi Digital Terhadap Kesiapan Mahasiswa Dalam Pendidikan Abad 21 - Tria Febriana; Agus Lestari (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Technological developments in the era of the Fourth Industrial Revolution (Industry 4.0) require university students to possess adequate digital literacy as part of 21st-century educational competencies. Digital literacy is not only related to the ability to operate devices, but also includes critical thinking, digital communication, creativity, collaboration, and information security. This study aims to analyze students’ readiness to face the challenges of 21st-century education through strengthening digital literacy. The analysis was conducted by reviewing various studies that discuss students’ digital literacy abilities, infrastructure barriers, the effectiveness of digital literacy training, and its relationship with soft skills and work readiness. The results indicate that students’ digital literacy falls within the sufficient to good category; however, gaps remain in technical skills and higher-order thinking abilities. Digital infrastructure, technology-based learning methods, and hands-on training have a significant influence on improving digital literacy. In addition, strong digital literacy must be balanced with soft skills such as communication, teamwork, and self-management so that students are prepared to face the dynamics of the VUCA era and competition in the job market. Therefore, higher education institutions need to strengthen learning strategies, digital facilities, and structured training programs to develop students’ digital literacy competencies comprehensively. Keywords: Digital literacy, student readiness, 21st-century education, technology-based learning, soft skills. Abstrak Perkembangan teknologi pada era Revolusi Industri 4.0 menuntut mahasiswa memiliki literasi digital yang memadai sebagai bagian dari kompetensi pendidikan abad 21. Literasi digital tidak hanya berkaitan dengan kemampuan mengoperasikan perangkat, tetapi juga mencakup kemampuan berpikir kritis, komunikasi digital, kreativitas, kolaborasi, serta keamanan informasi. Penelitian ini bertujuan untuk menganalisis kesiapan mahasiswa dalam menghadapi tantangan pendidikan abad 21 melalui penguatan literasi digital. Analisis dilakukan dengan mengkaji berbagai penelitian yang membahas kemampuan literasi digital mahasiswa, hambatan infrastruktur, efektivitas pelatihan literasi digital, serta keterkaitannya dengan soft skill dan kesiapan kerja. Hasil analisis menunjukkan bahwa literasi digital mahasiswa berada pada kategori cukup hingga baik, namun masih terdapat kesenjangan pada keterampilan teknis dan kemampuan berpikir tingkat tinggi. Faktor infrastruktur digital, metode pembelajaran berbasis teknologi, dan pelatihan praktik memiliki pengaruh signifikan terhadap peningkatan literasi digital. Selain itu, literasi digital yang kuat harus diimbangi dengan soft skill seperti komunikasi, kerja sama, dan manajemen diri agar mahasiswa siap menghadapi dinamika era VUCA dan persaingan dunia kerja. Dengan demikian, perguruan tinggi perlu memperkuat strategi pembelajaran, fasilitas digital, serta program pelatihan terstruktur untuk mengembangkan kompetensi literasi digital mahasiswa secara komprehensif. Kata Kunci: Literasi digital, Kesiapan mahasiswa, Pendidikan abad 21, Pembelajaran berbasis teknologi, Soft skill.